2019
DOI: 10.1111/eje.12438
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ intentions to manage drug users: Role of theory of planned behaviour and continuing education

Abstract: Objectives:To assess dentists' intention to manage drug users (DUs) and to evaluate the role of the theory of planned behavior (TPB) and continuing education (CE) in explaining this intention. Materials and Methods:A cross-sectional study was conducted in 2017, including dentists from three major Saudi cities. A questionnaire assessed personal and professional background and components of TPB: attitude, perceived social norms, perceived control and intention to manage DUs. Respondents expressed their agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Similarly, the TPB was previously used to explain compliance with tobacco free policy among university students [40] and predict smoking behaviors among students [41]. The advantages of using TPB for this study is that TPB provides a conceptual framework to explain behavior, which is crucial in guiding the development of training to prepare dental students to meet the needs of TCC [29]. Furthermore, TPB is characterized by several features that may help explain its widespread use as a model for the prediction and change of behavior [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the TPB was previously used to explain compliance with tobacco free policy among university students [40] and predict smoking behaviors among students [41]. The advantages of using TPB for this study is that TPB provides a conceptual framework to explain behavior, which is crucial in guiding the development of training to prepare dental students to meet the needs of TCC [29]. Furthermore, TPB is characterized by several features that may help explain its widespread use as a model for the prediction and change of behavior [42].…”
Section: Discussionmentioning
confidence: 99%
“…Intention, in turn, is related to the attitude toward this behavior, the perceived control over this behavior and the prevailing norms in the surrounding environment toward this behavior. The TPB was previously used to explain dentists' intention to engage in several behaviors such as managing drug users [29], reporting suspected violence against patients [30], managing HIV-positive patients [31] and adopting preventive precautions against COVID-19 [32]. The aim of this study was to assess Indonesian dental students' intention to provide TCC and whether this intention can be explained by the TPB.…”
Section: Introductionmentioning
confidence: 99%
“…These intentions, in turn, are affected by the control that people perceive they have over their actions, by their attitude toward the behavior and whether they think it is useful, important or desirable, and by the norms they perceive to be prevailing around them. The TPB was previously used to explain dentists' behaviors including delivering prevention [17], reporting suspected violence [18], and managing drug users [19]. The change in behaviors among dentists due to the COVID-19 pandemic may be explained by the TPB including the control they perceive they have over avoiding infection by the disease because of previous training they received, worries because of the pandemic which may affect their attitudes and the importance they attach to adopting preventive behaviors, and the prevailing norms around them regarding the seriousness of the pandemic based on the fatalities it causes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the TRA constructs, the TPB includes perceived behavioral control, therefore allowing a better explanation of behaviors which are beyond full volitional control and improved predictive power of the model [24,32]. Moreover,TPB has proved to be a reliable tool in predicting and explaining occupational behaviors [26,30,31,[33][34][35][36]. A systematic review revealed consistency of predicted behavior between health-care professionals and non-health-care professionals, indicating that TPB is a valid tool for use in the occupational context of health care [26].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported on residual effects of past behavior on intention and future behavior after having controlled for the original TPB constructs, suggesting that these effects reflect the sufficiency of the TPB model [40,41]. Only a few studies have considered the occupational behavior of dental health-care professionals using a socio-cognitive approach [33,34,36,42,43].…”
Section: Introductionmentioning
confidence: 99%